Analisis Faktor-Faktor Yang Mempengaruhi Kebijakan Dividen - Rahman, Olivia Anastasia; Hasanuddin, Hasanuddin; Abdullah, Julie (Universitas Gorontalo, 2022)
Dividend policy is a decision in using profits, whether the profits earned by the company will be distributed to shareholders as dividends or will be retained in the form of retained earning to finance investments in the future. The pharmaceutical sub-sector has a high investment realization value and in relation to dividends, investors definitely want a return, one of which is through dividends. This study takes 4 variabel as factors that influence dividend policy, including profitability (ROA), leverage (DER), liquidity (CR), and firm size. The research method uses multiple linear regression analysis with an observation period of 7 years.The results of the study reveal that simultaneously the variables of profitability (ROA), leverage (DER), liquidity (CR), and firm size have a significant effect on dividend policy in the pharmaceutical sub-sector. Partially, only the liquidity variable (CR) has a significant effect on dividend policy, while the profitability (ROA), leverage (DER) and firm size variables has no significant effect on dividend policy in pharmaceutical sub-sector.